Missile Guidance Design Using Sliding Curve Method - Wihardi, Leonard; Kadir, Rusdhianto Effendi Abdul; Hidayat, Zulkifli (2019 International Conference on Computer Engineering, Network, and Intelligent Multimedia (CENIM), 2019)
Missile guidance design problem for missile is considered in this paper. Guidance system is an important part of the missile to navigate it to reach and hit the target. The guidance system provides input to the autopilot to direct the missile flight. We proposed missile guidance design based on the sliding curve method to follow a specified path. In this method, the missile is guided according to a pre-determined trajectory by giving reference orientation angles to the missile autopilot system. The reference orientation angles are acquired through calculating the relative position between missile and the trajectory itself. Dubins curve is employed to create a smooth reference trajectory for the missile. The effectiveness of the method is shown by simulating the method a missile that flew following several paths.